The Importance of British Material Culture to Historical Archaeologies of the Nineteenth Century - Brooks, Alasdair (Society for Historical Archaeology Series in Material Culture, 2016)
Cover -- Title Page -- Copyright Page -- Contents -- List of Figures -- List of Tables -- Introduction: The Importance of British Material Culture to Historical Archaeologies of the Nineteenth Century -- 1. At the Center of the Web: Later Eighteenth- and Nineteenth-Century Ceramics from Huntingdon Town Centre in an International Context -- 2. Containers and Teapots: Archaeological Evidence for the Exported Wares of the Caledonian Pottery, Rutherglen, and Its Role in Glasgow's Ceramic International Trade and Industry -- 3. "A Trifling Matter"?: State Branding on Stoneware Bottles, 1812- 1834 -- 4. Uncovering and Recovering Cleared Galloway: The Role of Documents in Rural Eighteenth- and Nineteenth- Century Lowland Scotland -- 5. The Fall of Big Hair: Hair Curlers as Evidence of Changing Fashions -- 6. Food as Material Culture in a Nineteenth- Century Ecclesiastical Community, Worcester, England -- 7. "Perfection and Economy": Continuity and Change in Elite Dining Practices, ca. 1780- 1880 -- 8. Material Culture in Miniature: The Historical Archaeology of Nineteenth- Century Miniature Objects -- 9. Artifacts of Mortuary Practice: Industrialization, Choice, and the Individual -- 10. "Home"- Made: Exploring the Quality of British Domestic Goods in Nineteenth- Century Urban Assemblages -- 11. Shadows after Sunset: Imperial Materiality and the Empire's Lost Things -- Contributors -- Index.